A cross-cultural examination of the intention to use technology between Singaporean and Malaysian pre-service teachers: an application of the Technology Acceptance Model (TAM) - Teo, Timothy; Wong, Su Luan; Chai, Ching Sing (International Forum of Educational Technology & Society, 2008)
As computers becomes more ubiquitous in our everyday lives, educational settings are being transformed where educators and students are expected to teach and learn, using computers (Lee, 2003). This study, therefore, explored pre-service teachers’ self reported future intentions to use computers in Singapore and Malaysia. A survey methodology was employed such that validated items from past relevant research work were adopted. Based on the Technology Acceptance Model (TAM), 495 completed surveys of pre-service teachers were collected from both countries. Structural Equation Modeling (SEM) was implemented on the data captured. This study contributes to the growing multi-cultural studies on TAM by demonstrating that perceived usefulness (PU), perceived ease of use (PEU) and computer attitudes (CA) to be significant determinants of both Singaporean and Malaysian pre-service teachers’ behavioral intention (BI). Differences were, however, detected between Singaporean and Malaysian pre-service teachers in terms of PU, PEU and CA but no differences were detected in BI with regards to technology acceptance.